New Approach to Economic Convergence in the EU: A Multilevel Analysis from the Spatial Effects Perspective. (May 2019) - Díaz Dapena, Alberto; Rubiera-Morollon, Fernando; Paredes, Dusan
The β-convergence model is based on the neoclassical framework in which the spatial level of analysis is not relevant. These levels will result in decreasing returns. However, local processes of agglomeration, spillover effects, or other forces could operate differently depending on the level of spatial disaggregation. The primary objective of this article is to observe whether different local, regional, and national convergence behaviors are possible in the European Union (EU). To capture the differences among spatial scales, a multilevel and spatial effects extension of the Solow–Swan theoretical growth model is proposed. The estimations of this model are made using consistent information from Eurostat and Cambridge Econometrics for the period of 2000–2014. A multilevel spatial Durbin model estimator is applied to evaluate the spatial interactions of the regions. The results indicate that a general process of convergence in the EU coexists with intranational processes of divergence, highlighting the relevance of the spatial level of analysis. A final analysis of the impact of the economic crisis over the general behavior has been included verifying that the economic crisis strongly reinforce the weakness of the EU convergence.